0
$\begingroup$

Could someone verify this proof? Prove $\lim\limits_{n\to\infty} C_n = \lim\limits_{n\to\infty} \dfrac{4n+3}{7n-5} = \dfrac{4}{7}$

Proof: Let $\epsilon > 0$ and take $N = \dfrac{41}{49\epsilon} + 1$ This implies that for all $n > \dfrac{41}{49\epsilon} + 1 \iff n-1 > \dfrac{41}{49\epsilon} \iff \epsilon(n-1) > \dfrac{41}{49} \iff \epsilon > \dfrac{41}{49n - 49} \iff$

$ \iff \epsilon > \dfrac{41}{49n-35} \iff \epsilon > \dfrac{28n+21-28n+20}{49n-35} \iff \dfrac{7(4n+3)-4(7n-5)}{7(7n-5)} \iff \epsilon > \dfrac{4n+3}{7n-5}-\dfrac{4}{7} \iff \epsilon >|\dfrac{4n+3}{7n-5}-\dfrac{4}{7}|$

End of proof

$\endgroup$
2
$\begingroup$

This is correct I guess, but extremely tedious. I would never actually prove a limit exists this way when we are dealing with quotients of polynomials. The standard thing to do is prove the following theorem:

Theorem. If $\lim\limits_{n \to \infty} a_n = A$ and $\lim\limits_{n \to \infty} b_n = B$ and $c\in \mathbb{R}$ then $$ \lim\limits_{n \to \infty}(c a_n) = c A \text{ as long as $cA \neq 0 \cdot \infty$} $$ $$ \lim\limits_{n \to \infty}(a_n + b_n) = A + B \text{as long as $A + B \neq \infty - \infty$} $$ $$ \lim\limits_{n \to \infty}(a_n b_n) = AB , \text{ as long as $AB \neq 0\cdot \infty$} $$ $$ \lim\limits_{n \to \infty}\frac{a_n}{b_n} = \frac{A}{B}, \text{ as long as $B \neq 0$ and not $B=A=\infty$}. $$

One you have this theorem we can write $$\frac{4n+3}{7n-5} = \frac{4 + \frac{3}{n}}{7 - \frac{5}{n}}$$ for all $n \neq 0$. Applying the quotient of limits part of the previous theorem we find $$ \lim_{n \to \infty}\frac{4n+3}{7n-5} = \lim_{n \to \infty}\frac{4 + \frac{3}{n}}{7 - \frac{5}{n}} = \frac{\lim\limits_{n \to \infty}(4+\frac{3}{n})}{\lim\limits_{n \to \infty}(7 - \frac{5}{n})} = \frac{4+0}{7+0} = \frac{4}{7}. $$

$\endgroup$
0
$\begingroup$

I would work forwards, not backwards starting with magic constants.

We want to show that $lim_{n \to \infty} \frac{4n+3}{7n-5} = \frac{4}{7}$.

$\frac{4n+3}{7n-5} - \frac{4}{7} = \frac{7(4n+3)-4(7n-5)}{7(7n-5)} = \frac{28n+21-28n+20}{49n-35} = \frac{41}{49n-35} $.

To make this to be less than $c$ for any real $c$, choose $n$ such that $\frac{41}{49n-35} < c$ or $41 < 49cn-35c$ or $n > \frac{41+35c}{49n}$.

$\endgroup$
-1
$\begingroup$

I have the same issue when it comes to proving limits with the inequality theorem.

I'm not sure the above is a proof by first principles though i.e. using the epsilon- delta method. Is there a way to explain how to use the ineuality theorem using first principles?

$\endgroup$
  • $\begingroup$ This is not an answer. Please refrain from writing this as an answer, this is more of a comment if anything. $\endgroup$ – AmorFati Nov 23 '17 at 11:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.